Uruguay : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper examines the performance of Uruguay's exports, external balances, and relative price movements over the past decade and applies the IMF's standard external sector assessment tools to Uruguay. The results indicate that Uruguay has made important strides in export performance, including expanding markets shares over the past decade, driven by trade competitiveness gains. The current account deficit has remained well contained and more than fully financed by foreign direct investment over the past decade, notwithstanding external shocks. At the same time, the real exchange rate has appreciated strongly in recent years. Standard IMF equilibrium real exchange rate valuation models also suggest that the Uruguayan peso is slightly stronger than its equilibrium level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet